View of part of the ancient remains of London Wall - Schnebbelie, Robert Blemmell; Dale (Tufts Archival Research Center, 2008)
Near Postern Row, Tower Hill, in September 1818, with a plan of Postern Row. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.